The Influence of Company Values on Customer Satisfaction with Perceived Service Quality as a Moderating Variable - Tambunan, Damelina Basauli; Widyadhari, Amalia Tiffany (International Business Management - Universitas Ciputra, 2024)
This study is specifically aimed at examining the effect of company values on customer satisfaction which is moderated by perceived service quality. This study uses the theory of Social Cognitive Theory for the phenomenon of indications for customers being dissatisfied with the services provided by companies that offer services. This study uses a quantitative approach through the distribution of questionnaires with research samples are individuals who are appointed and trusted by each company who have enjoyed the services of PT. Aperindo Prima Mandiri as many as 8-9 people 17 companies and samples that were successfully collected according to the criteria were 141 respondents. The method used in this research is SPSS. The results of the research show that Company Values have a significant effect on the Customer Satisfaction variable. This indicates that Company Values are important factors that can affect Customer Satisfaction. Perceived Service Quality weakens the relationship between Company Values and Customer Satisfaction variables. This indicates that the existence of Perceived Service Quality is able to weaken the effect of the relationship between Company Values on Customer Satisfaction. Overall, the results of this study indicate that there is a negative relationship between the company values, interaction variable and perceived service quality on customer satisfaction.